A produção pesqueira e o esforço da pesca no município de Manaus (Amazonas-Brasil): análise e proposta de melhorias para viabilizar a industrialização - (:unkn) unknown (Universidade Federal do Amazonas, 2017)
The fishing in the Amazon constitutes one of the main economic activities. In addition to contribute to the animal protein supply as also the labor work ocupation, the income generation and the state collection. Besides its effort, the resulting production from the extractive fishing, as well as the pisciculture, still aren’t capable to supply the local demand and there already is indication of overfishing for some species. And still, it’s possible to notice that in the fishing sector, some aspects of the productive system may being controlled while others, like the hydrological cycle are out of control from individuals and it’s administrator. This work’s analyzed data indicate a positive correlation between the fishing production and the river’s maximum and minimum level to the level of 95% of trust. The intensity of this relation is weak, the calculated r value was 57,2%. The calculeted determination coefficient resulted in r2=0,327, in other words, only 32,7% of variability on the fishing production results may be explained by the river’s level and 67,3% of the total variability is due the other factors that weren’t investigated. Therefore, these results makes unfeasible the determination of a equation model that may be used to provide production expectations. As it remits us to the conclusion that the river’s level affects the fishing production this, however, it’s a general hypothesis and hard to be tested, once that the particular state of each stock involved on fishising, can’t be measured from the total production data when it’s about a multivariate fishing, as it`s in Manaus, because there may be underexploited and overexploited stocks.
Keywords: Pesca; Produção Pesqueira; Rio Negro (AM); ENGENHARIAS: ENGENHARIA DE PRODUÇÃO